RNA Amplification Strategies for cDNA Microarray Experiments. (February 2003) - Wang, J.; Hu, L.; Hamilton, S.R.; Coombes, K.R.; Zhang, W.
The biological materials available for cDNA microarray studies are often limiting. Thus, protocols have been developed to amplify RNAs isolated from limited amounts of tissues or cells. RNA amplification by in vitro transcription is the most widely used among the available amplification protocols. Two means of generating a dsDNA template for the RNA polymerase are a combination of reverse transcription with conventional second-strand cDNA synthesis and a combination of the switch mechanism at the 5′ end of RNA templates (SMART) with reverse transcription, followed by PCR. To date, there has been no systematic comparison of the efficiency of the two amplification strategies. In this study, we performed and analyzed a set of six microarray experiments involving the use of a "regular" (unamplified) microarray experimental protocol and two different RNA amplification protocols. Based on their ability to identify differentially expressed genes and assuming that the results from the regular protocol are correct, our analyses demonstrated that both amplification protocols achieved reproducible and reliable results. From the same amount of starting material, our results also indicated that more amplified RNA can be obtained using conventional second-strand cDNA synthesis than from the combination of SMART and PCR. When the critical issue is the amount of starting RNA, we recommend the conventional second-strand cDNA synthesis as the preferred amplification method.